If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12(x-1)=11(x+2)
We move all terms to the left:
12(x-1)-(11(x+2))=0
We multiply parentheses
12x-(11(x+2))-12=0
We calculate terms in parentheses: -(11(x+2)), so:We get rid of parentheses
11(x+2)
We multiply parentheses
11x+22
Back to the equation:
-(11x+22)
12x-11x-22-12=0
We add all the numbers together, and all the variables
x-34=0
We move all terms containing x to the left, all other terms to the right
x=34
| x÷8×22=680 | | 5(x-4)+2x=22 | | 13=-7u+5(u+5) | | x÷8(22)=680 | | 4x^2=-x^2-10x+75 | | -4d+14=-2 | | 12a+17=4a+1 | | h/4=-10 | | 5t–3=7 | | 3×+4=-2(6x-8) | | 2x+9=2x+29 | | (y-6)^2=48 | | (y-6)^2-48=0 | | 15a-20+a=44 | | 4(2x^2)=82 | | 3x+0.4=21.4 | | x3(x+6)=−12 | | 8-3c=17 | | 6u2-24u=0 | | x+4=-x-6 | | 6x−2x−28=11x | | 14040-50x=12500-20 | | 14,040-50x=12,500-20 | | 2x^2-4x-110=0 | | -3/2x(-51/4)= | | 0.4p=0.2 | | -m/23+7=32 | | (3x+7)+82=180 | | 1.2w=0.2+12 | | -64=-1/4x | | c=2(3.14)(8.5) | | 4x-5/3=1/2(2x-6)/6 |